Samantha Riley's Full Stroke at 70 m of Her Sixth Place 100 m Breaststroke Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (12 frames) and the appropriate technical/ biomechanical explanations for Samantha Riley's Full Stroke at 70 m of Her Sixth Place 100 m Breaststroke Race at the 1998 Perth World Championships. The reason for presenting Samantha Riley in this forum is that she has been World Champion and world record holder. She is the reigning Pan Pacific champion. Her swims at Perth were "disappointments" and were largely attributed to the after effects of tonsillitis. However, her times still do not match those of 1994 and it is worthwhile to evaluate her stroke to determine if there are any possible technical faults that might have stalled her progress. Samantha Riley's stroke demonstrates several detrimental faults that if corrected could produce great improvements. Several improvements are possible in this stroke. They would likely produce performance time improvements of a significant nature.